Neoliberalism: Befall or respite? - Josifidis Kosta; Lošonc Alpar; Supić Novica (Panoeconomicus, 2010)
The authors of this argumentative article emphasize that the range of the current crisis cannot be depleted in the diagnosis which is based on cyclic consideration. It is both systematic and structural, which is derived from the genesis and the modus of neoliberalism, which has become dominant during the previous decades. Other than that, it is emphasized that the current crisis is 'great', because it forces relevant actors to face the structural characteristics of contemporary shareholder-capitalism. The crisis also puts to a test the self-reflection of the economic science which faces certain deficits. The authors believe that, given the tendencies in today's economy, there can be different scenarios for exiting the crisis and projecting a new modus of capitalism in the following period. Having in mind the openness of the present and the uncertainty of the future, the authors describe those scenarios without projecting which one of them will be dominant.